2010
DOI: 10.1038/cr.2010.180
|View full text |Cite
|
Sign up to set email alerts
|

Mouse cloning and somatic cell reprogramming using electrofused blastomeres

Abstract: Mouse cloning from fertilized eggs can assist development of approaches for the production of "genetically tailored" human embryonic stem (ES) cell lines that are not constrained by the limitations of oocyte availability. However, to date only zygotes have been successfully used as recipients of nuclei from terminally differentiated somatic cell donors leading to ES cell lines. In fertility clinics, embryos of advanced embryonic stages are usually stored for future use, but their ability to support the derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Furthermore, fetal lipid deposition is mainly increased in the gestational period (Haggarty, 2002 ). During the course of reproduction, pre-implantation stages are important for reproductive and stem cell biology (Riaz et al, 2011 ). The UBTFL1 gene, also known as Hmgpi , is a preimplantation-specific gene and is involved in early development and implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fetal lipid deposition is mainly increased in the gestational period (Haggarty, 2002 ). During the course of reproduction, pre-implantation stages are important for reproductive and stem cell biology (Riaz et al, 2011 ). The UBTFL1 gene, also known as Hmgpi , is a preimplantation-specific gene and is involved in early development and implantation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mouse zygotes and electro-fused blastomeres arrested in mitosis can acquire a reprogramming capacity in SCNT (Egli et al, 2007;Riaz et al, 2011). However, a recent study has shown that even the cytoplasm of interphase twocell mouse embryos can reprogram somatic cells in SCNT, if the donor nucleus and recipient cytoplasm are synchronized (Kang et al, 2014).…”
Section: Mitosis As a Window Of Opportunity For Changes In Cell Fatementioning
confidence: 99%
“…However, these poorly defined maternal factors presumably decline sharply after fertilization since cytoplasm of pronuclear stage zygotes is reportedly inactive 4 , 5 . Recent evidence suggests that zygotic cytoplasm, if maintained at metaphase (M-phase) can also support derivation of embryonic stem cells (ESCs) following SCNT 6 - 8 , albeit at low efficiency. This led to the conclusion that critical oocyte reprogramming factors present in M-phase but not in interphase cytoplasm are “trapped” inside the nucleus during interphase and effectively removed during enucleation 9 .…”
mentioning
confidence: 99%